FAKTOR-FAKTOR PERKEMBANGAN PERMUKIMAN DI KECAMATAN RAMBATAN KABUPATEN TANAH DATAR - Muhammad Fadhlillah; Rery Novio (JURNAL BUANA, 2020)
This research aims to find out settlement patterns and review factors of development settlements in the Rambatan Subdistrict, Tanah Datar Regency. This type of research is quantitative descriptive with the population is the head of the family in the Rambatan Subdistrict. Determination of sample size using the Slovin formula so that a sample of 75 settlement points was obtained. The sampling technique used was simple random sampling. Data collection techniques using secondary data with data analysis techniques, namely nearest neighbor analysis. Nearest neighbor analysis done by giving points to each variable used in the study. The factors of settlement development in this study were measured by physical factors and social factors. Physical factors are natural factors, location factors, transportation factors and accessibility. Social factors are population growth factors and economic factors. The results of the analysis of the factors of settlement development are known that the settlement patterns of the Rambatan Subdistrict are included in the clustered classification, physical factors and social factors influence the slow development of settlements in the Rambatan Subdistrict.